SIMULATION OF CHANGES IN VISCOSITY HEAVY WASTE TRANSPORT - Gii Benitez, W. (1998)
This study analyzes the mechanisms which cause the increment of viscosities in the residuals of heavy oil during the process of transfer and transport. lt has been determined that the increment is dueto the loss of the viscoreducer which is cause by vaporization. These loss of viscosity is a double logarithmic function of the concentration (expressed in volume) of the viscoreducer. lt is recommended to establish a norm of quality control of residuals to achieve a bener behaviour of the product, determining the temperature of 6% of volume and the viscosities from this cut at 1002F and 210°F.